International trade : on the brink of change - Anita Maček (International trade : on the brink of change, 2017)
Based on previous observations, there is no doubt that trade enhanced economic growth. This is especially valid in regard to international trade as it can help or hinder entire regions, thus adding to the issue of international security. In this book, we tried to collect texts that would not repeat known facts on international trade but would rather discuss special issues. Furthermore, we also wanted to bring regional perspectives. Therefore, this book is organized into two sections: "Selected Perspectives on International Trade" and "Regional Specific Issues of International Trade".
10.5772/63143; 10.5772/63143